BEP: Bit error pattern measurement and analysis in IEEE 802.11 - LI, Jiayue (Institutional Knowledge at Singapore Management University, 2015)
The IEEE 802.11 is a set of Media Access Control (MAC) and Physical Layer (PHY) specifications which concern the Wireless Local Area Network (WLAN) service. However, most IEEE 802.11 WLAN services are easily affected by external elements, such as the homogeneous interference caused by the high-density deployment of IEEE 802.11 devices, the attenuation effect caused by complicated indoor obstacles, and the heterogeneous interference caused by other devices which operate out of unlicensed 2.4GHz ISM bands. In this paper, we first present a method to capture IEEE 802.11n Bit Error Patterns (BEP) under the network effect such as the homogeneous interference and the signal attenuation caused by obstacles. We separate the two issues by showing the specific BEP distributions under different channel conditions. In addition to the IEEE 802.11n BEP analysis, we further simulated the impact of the LTE-Unlicensed (LTE-U) signal to the IEEE 802.11ac at the 5GHz, and analyzed similar BEPs through a purely experiment based method.